PSEUDO-TERNARY PHASE DIAGRAMS OF A DRUG DELIVERY SYSTEM - Wang, Ziheng (University of Waterloo, 2009)
The purpose of this research was to develop the pseudo-ternary phase diagrams for a model drug delivery system consisting of vitamin E (model drug) + soybean oil + surfactant + co-surfactant (anhydrous glycerol) + water. The model drug (vitamin E) was loaded in the oil phase. The effects of different surfactants (pure and mixed) on the phase diagram, especially the microemulsion region, were investigated. The influence of drug loading level on the phase diagram was also determined. The surfactants studied were Tween 20, Tween 80, Cremopher EL, and their mixtures. The size (area) of the microemulsion region of the phase diagram was found to be dependent on the type of surfactant used and the loading level of drug (vitamin E). The phenomenon of phase inversion from W/O microemulsion to O/W microemulsion was also investigated for the drug delivery system consisting of soybean oil (0% w/w Vitamin E loading or 30% w/w Vitamin E loading) + Tween 80 + anhydrous glycerol + water. The inversion of phases was detected by observing changes in the viscosity of the system.
Keywords: Microemulsion; Psesudo-ternary phase diagram; drug delivery; Chemical Engineering